Sobre un caso de simpatoma simpatoblástico del estómago - Bianchi, Andrés E. (1937)
The authors study a case of this kind of blastomatas in a woman 63 years old ; the blastomata had the seize of a little orange, having a kind evolution clinic, in spite of his gastric localization. With this motif, the authors study all the nervous tumors of the sympatetic system and they make a general revision of the bibliographic, establishing a total of nine observations similars to those studied by them.